Preliminary Screening of Hydrogel Containing Martynia annua Extract for Anti-Inflammatory Activity - Jain, Dr. Alok Pal (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The aim of the present study was to investigate the preliminary evaluation of hydrogel formulation of methanol fraction of Martynia annua for anti-inflammatory activity using different types of animal models. Materials and Methods: Five different hydrogel formulations containing extract and one control without extract were prepared according to standard method using different proportions of Carbopol 940 and sodium CMC. Prepared hydrogel was characterized for optimization and screened for anti-inflammatory activity using xylene-induced ear edema and croton oil-induced ear edema in mice. Effect was observed by the measurement of percent inhibition of ear edema and biochemical parameters, for example, nitric oxide level and MPO level. Results: Phytochemical screening showed that petroleum ether extract of Martynia annua showed the presence of sterols, terpenoids, and fatty oils while the ethanol extract showed the presence of glycosides, phenolic compounds, flavonoids, and amino acids. Results of all other evaluation parameters, for example, pH, viscosity, spreadability, and consistency were found suitable in optimized formulation as 1.5 g of Carbopol 940 and 1% of sodium CMC for best drug release profile. Effect of MAMFH was observed greater percentage of edema inhibition (66.67%) and was comparable to standard group of treatment (65.59%). Results showed that MPO level of inflamed ears (inflamed control, treated only with gel base) was significantly higher in comparison with the non-inflamed control (P < 0.01) and with hydrogel formulations. The results showing the ability of croton oil to induce neutrophil influx into mice ear tissue. This may be reduced by treatment with extract hydrogels, as well as Voltaren Emulgel, reduced significantly (P < 0.05) the MPO levels in mice ears. Conclusion: Methanol fraction of Martynia annua was capable of inhibiting ear edema induced by xylene. It may be due to the ability of extract to either inhibit the synthesis, release, or action of xylene involved in the inflammation. Methanol extracts were exhibits its anti-inflammatory action by inhibiting the synthesis, release, or action of histamine. Significant activity may be due to the presence of flavonoids in methanol extract fraction of Martynia annua leaves.